The Verification of HF Signal Transmission via Grounding System for Online PD Measurement - Srinangyam, Chissanupong; Pannil, Pittaya; Thungsook, Kittisak; Promwong, Sathaporn; Nimsanong, Phethai; Pattanadech, Norasage (My University, 2022)
This paper discusses signal transmission in the grounding system. During online partial discharge (PD) measurement for the high voltage (HV) apparatus, various PD pulse currents recharge the dielectric of HV apparatus when a PD occurs. One of the noise typologies that affects PD patterns is called the cross-talk, that is, discharges that appear in the measured point due to coupling from another point. In order to study the cross-talk signal, the two PD measuring circuits which are circuit no.1 and circuit no.2, on the same grounding system in the HV laboratory were performed. The distance between two PD measuring circuits is about 20 meters. The artificial PD models were utilized to generate the PD signal injecting to the test circuit no.1, while the cross-talk signals were investigated in circuit no.2. The HFCT sensors were used to measure the PD signal in circuit 1 and the cross-talk signal in circuit 2. The measurement results found that the cross-talk signal transmission in grounding systems provides a bipolar PRPD pattern, and the pulse waveform shows an oscillation shape. Moreover, onsite PD measurements of the generator steam turbine were studied. It is noticeable that the knowledge about cross-talk phenomena in grounding systems can help the PD verification and location for online PD measurement.
Keywords: Cross-talk PD; HFCT; Online PD measurement; PD diagnosis; PRPD; TF-map